THE EFFECT OF DIVIDEND POLICY, LIQUIDITY, PROFITABILITY AND FIRM SIZE ON FIRM VALUE IN FINANCIAL SERVICE SECTOR INDUSTRIES LISTED IN INDONESIA STOCK EXCHANGE 2015-2018 PERIOD - Sondakh, Renly (Universitas Sam Ratulangi, 2019)
Firms that go public have a target to increase the value of their firm, because the value of the firm is an attractive factor for investors to call their capital. Firm value is a financial indicator because high corporate value can prove prosperity for shareholders. This study attempts to analyze the dividend, liquidity, profitability and size of the firm policy on the value of the firm. This research was conducted on financial services companies listed on the Indonesia Stock Exchange for the period 2015-2018, including 12 companies that met the sample requirements by using purposive sampling from 99 financial service companies for the 2015-2018 period. This study uses multiple linear regression data analysis received with the SPSS program which contains the classic assumption test, partial test (t-test). The results of this study indicate that dividend policy has a negative and significant effect on firm value, liquidity and firm size partially influence positively and significantly on firm value while profitability is not appropriate and not significant to firm value.